Ozonioterapia na medicina veterinária e sua ação antibacteriana na cistite canina - Engelmann, Ana Martiele (2023)
This doctoral thesis was divided into three parts, resulting in two manuscripts and a scientific article. The first manuscript consisted of verifying the main prescriptions of treatments with medicinal ozone in the small animal clinic, in addition to verifying the profile of the professional who prescribes. To this end, structured questionnaire was made available on a digital platform during April and May 2021. The research was carried out through social networks and forwarded to the Residency and Postgraduate Programs in Veterinary Medicine in the three southern states of Brazil (Rio Grande do Sul, Santa Catarina and Paraná), as well as veterinarians from clinics and hospitals who provide home care. Among the 213 research participants, 98.1% claimed to use at least one integrative therapy in clinical practice, with the most used being physiotherapy (81.7%), acupuncture (80.3%) and ozone therapy (OZT) (68.5%). Among the participants, 72.0% claimed to apply or recommend ozone therapy. The main diseases treated with OZT were healing of open wounds (91.1%), dermatitis (63.7%), asepsis of contaminated wounds (46.6%) and post-surgical healing (49.7%). Among the participants who do not apply/recommend it, the main reasons were the lack of proof of effectiveness (38.6%) and the lack of technical knowledge of the professional (35.1%). The second manuscript aimed to evaluate the in vitro antimicrobial activity of the ozonized saline solution (O3SS) over standard strains and on resistant or multi-drug resistant isolates commonly associated with cystitis in dogs. For this, the plating method was used to evaluate the antimicrobial activity of exposure for 60 seconds of O3SS at 78 µg mL-1 on standard strains (Staphylococcus aureus and Escherichia coli) and multiresistant isolates (Proteus mirabilis, Klebsiella sp. and Enterococcus sp.), and the broth microdilution test to determine the minimum inhibitory and bactericidal concentration for strains of S. aureus, E. coli and Pseudomonas aeruginosa in the same solution. Plating was the only assay in which treatment with O3SS resulted in bactericidal activity, promoting a reduction greater than 99% of colony forming units for most strains collected, except for P. mirabilis. The third study aimed to report the effectiveness of two different protocols of bladder irrigation with O3SS in a paraplegic canine with recurrent bacterial cystitis caused by Proteusspp. The first treated approach applied, which consisted of repeated instillations of 60 mL of O3SS at 59 µg mL-1 , once a day, for three consecutive days, was not effective. On the other hand, the second protocol used, which consisted of successive washes in a single day, respecting an interval of 2 hours between them, resulted in a significant reduction in the presence of bacteria in urine sedimentoscopy and in urine culture. In general, the data from this study provide a range of potential uses of OZT in the medical clinic of small animals that can be explored mainly by the scientific community to outline future experimental studies, seeking to consolidate knowledge about medicinal ozone in veterinary medicine.